2002
DOI: 10.1590/s1516-35982002000800027
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho produtivo de ovinos alimentados com dietas à base de feno de gramíneas tropicais

Abstract: 32 animais da raça Santa Inês (16 machos e 16 femeas) com peso médio de 26,5 kg. Utilizou-se o delineamento inteiramente casualizado, com quatro repetições, sendo cada repetição composta por dois animais. Os animais apresentaram respostas semelhantes para todos os parâmetros avaliados. O ganho de peso foi semelhante entre as dietas estudadas, sendo o valor médio para ganho de peso de 95 g/animal/dia. Não foram observadas diferenças nos consumos de matéria seca e fibra detergente neutro entre as várias dietas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
3
1
1
3
Order By: Relevance
“…The average intake of neutral detergent fiber, in kg/day and g/kg of BW was 0.503 kg/day and 19.6 g/kg of BW, respectively. Similar results to those obtained in this study were reported by Camurça et al (2002), who observed mean values of 515.04 kg/day and 18.2 g/kg of BW, respectively.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The average intake of neutral detergent fiber, in kg/day and g/kg of BW was 0.503 kg/day and 19.6 g/kg of BW, respectively. Similar results to those obtained in this study were reported by Camurça et al (2002), who observed mean values of 515.04 kg/day and 18.2 g/kg of BW, respectively.…”
Section: Resultssupporting
confidence: 93%
“…The higher intake of crude protein for mesquite pod meal, sorghum meal and wheat meal treatments is due to the intake of concentrate supplement, supplied at 10 g/kg of BW, with an average of 227.0 g/kg of CP. The mean value for the treatment with concentrate supplementation was 0.100 kg/day; this result was lower than that obtained by Camurça et al (2002), who evaluated the intake of sheep fed urochloa Grass supplemented with concentrate at 10 g/kg of BW and obtained an intake of crude protein of 0.151 kg/day. These higher values of crude protein intake are explained by the high crude protein content (CP) of the concentrate used by the authors (335.0 g/kg of CP).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Esses resultados foram semelhantes aos obtidos por Camurça et al (2002), que observaram valores médios de 515,04 g/ animal/dia, 1,82%PV e 41,97g/UTM, trabalhando Tabela 5 -Consumo de proteína bruta de ovinos alimentados com dieta contendo diferentes níveis de farelo de castanha de caju na ração concentrada e equações de regressão Tabela 4 -Consumo de matéria seca de ovinos alimentados com dieta contendo diferentes níveis de farelo de castanha de caju (FCC) na ração concentrada e equações de regressão (1994) justifica-se, pois espera-se que dietas contendo maiores níveis de farelo de castanha apresentem maior densidade energética. Dessa forma, as dietas contendo menores níveis de farelo de castanha seriam mais consumidas, na tentativa de se atingir a ingestão ótima de energia.…”
Section: Consumo De Fibra Em Detergente Neutrounclassified
“…Estes dados confirmam os resultados obtidos por Camurça et al (2002), que não observaram diferenças no ganho de peso de ovinos Santa Inês machos e fêmeas. Esse autor argumenta que a provável explicação para esse fato seria a limitação no fornecimento de nutrientes pelas dietas fornecidas.…”
Section: Ganho De Peso E Conversão Alimentarunclassified